Bacterial growth and biological properties of Cymbopogon schoenanthus and Ziziphus lotus are modulated by extraction conditions. (October 2020) - Rocchetti, Gabriele; Alcántara, Cristina; Bäuerl, Christine; García-Pérez, Jose V.; Lorenzo, José M.; Lucini, Luigi; Collado, María Carmen; Barba, Francisco J.
Graphical abstract: Highlights: C. schoenanthus and Z. lotus source of natural anti-inflammatory and antimicrobials. Extraction methodology and solvent used strongly affected the bacterial growth. The "plant species" main parameter in determining the biological properties observed. Z. lotus extracts showed higher polyphenolic contents than C. schoenanthus extracts. Polyphenols showed significant correlations with the antimicrobial properties. Abstract: The present study aims to evaluate the antibacterial activity and biological properties of two traditional Saharian plants ( Cymbopogon schoenanthus and Ziziphus lotus). The plant extracts were obtained by using a different combination of extraction methods (conventional vs. ultrasound-assisted) and solvents (water vs. ethanol:water (50:50, v/v)). The antioxidant profile, anti-inflammatory activity and impact on bacterial growth (foodborne and probiotic bacteria) of the obtained extracts were assessed. The plant species showed the hierarchically more important role in determining the biological properties of the extracts, followed by extraction solvent and extraction conditions. Conventional Z. lotus hydroethanolic extracts showed the highest total phenolic content (20.4 mg GAE/g), while Z. lotus ethanol extracts from ultrasound-assisted process presented the highest content of carotenoids (0.15 mg/g). In addition, ultrasound-assisted Z. lotus hydroethanolic extracts presented the highest in vitro radical scavenging activity, being 7.93 mmol Trolox/g. Multivariate analysis statistics (PCA) showed that both the extraction methodology and the solvent used strongly affected the bacterial growth. Z. lotus mainly decreased the growth rate of S. aureus and L. innocua. Interestingly, the aqueous extracts of this plant as well as those from C. schoenanthus, obtained by conventional extraction, significantly increased the growth rate and the maximal optical density of L. casei. Aqueous extracts of both Z. lotus and C. schoenanthus slightly influenced the growth of Bifidobacterium. Overall, the extracts of these plants showed selective activities with respect to pathogens and probiotic bacteria and may provide an advantage both in terms of antimicrobial and prebiotic activity.